Actemra Therapy and Survival Outcomes in Critically Ill COVID-19 Patients: A Retrospective Analysis - Mohammed, Monier; M. Khalifa, Aimen; Ali S. Abbas, Ghada; M.K. Abdeldaim, Guma (Libyan Journal of Public Health Practices, 2026)
Tocilizumab (Actemra), an interleukin-6 receptor antagonist, has demonstrated potential as a therapeutic option for severe COVID-19 by mitigating the hyperinflammatory response associated with disease progression. This study aimed to assess the impact of Actemra therapy on survival outcomes among hospitalized patients with severe or critical COVID-19 in a real-world setting. A retrospective observational cohort study was conducted at a COVID-19 isolation center in Al-Marj City, Libya. Adult patients with severe or critical COVID-19 admitted between August 2020 and Decamber 2021 were included. Data on demographics, clinical status, and laboratory results were extracted from medical records. The primary outcome was survival status, with secondary outcomes being hospital stay length and hospitalization-free survival time. A total of 195 patients were included (median age 58 years; 71.3% male), of whom 26.2% received Actemra. The Actemra group had higher ICU admission rates, gastrointestinal symptoms, and CPAP use, but reduced the prevalence of diabetes and hypertension. Actemra recipients experienced longer hospital stays and higher levels of inflammatory markers. Kaplan–Meier analysis revealed significantly longer survival in the Actemra group (mean 29.9 vs. 10.1 days, p < 0.001). Cox regression indicated a 77% reduction in hospitalization risk with Actemra (HR 0.230, p < 0.001). Logistic regression showed over fourfold increased survival odds (OR 4.552, p = 0.001). The study concluded that Actemra therapy significantly improved survival and reduced hospitalization risk in severe and critical COVID-19 patients. These findings support its targeted use in hyper inflammatory patients, with further randomized trials needed to confirm benefits and safety.